1994
DOI: 10.1038/ng0594-85
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the VHL tumour suppressor gene in renal carcinoma

Abstract: Multiple, bilateral renal carcinomas are a frequent occurrence in von Hippel-Lindau (VHL) disease. To elucidate the aetiological role of the VHL gene in human kidney tumorigenesis, localized and advanced tumours from 110 patients with sporadic renal carcinoma were analysed for VHL mutations and loss of heterozygosity (LOH). VHL mutations were identified in 57% of clear cell renal carcinomas analysed and LOH was observed in 98% of those samples. Moreover, VHL was mutated and lost in a renal tumour from a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
995
2
25

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,571 publications
(1,064 citation statements)
references
References 18 publications
42
995
2
25
Order By: Relevance
“…The most frequent genetic change in RCC is somatic inactivation of the VHL TSG (usually be mutation and loss, but promoter methylation may also occur), although VHL inactivation is specific for clear cell RCC (Foster et al, 1994;Gnarra et al, 1994;Clifford et al, 1998). Combining the results of the current study with previous investigations, frequent epigenetic changes (X20%) in RCC include promoter methylation of RASSF1A, TIMP3, DAPK, SLIT2, MT1G and GSTP1 (Esteller et al, 2001a;Nojima et al, 2001, Dreijerink et al, 2001Morrissey et al, 2001, Morris et al, 2003.…”
Section: Discussionsupporting
confidence: 63%
“…The most frequent genetic change in RCC is somatic inactivation of the VHL TSG (usually be mutation and loss, but promoter methylation may also occur), although VHL inactivation is specific for clear cell RCC (Foster et al, 1994;Gnarra et al, 1994;Clifford et al, 1998). Combining the results of the current study with previous investigations, frequent epigenetic changes (X20%) in RCC include promoter methylation of RASSF1A, TIMP3, DAPK, SLIT2, MT1G and GSTP1 (Esteller et al, 2001a;Nojima et al, 2001, Dreijerink et al, 2001Morrissey et al, 2001, Morris et al, 2003.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, the epigenetic inactivation of HOXB13 is independent of the VHL status. This may help us to elucidate the tumorigenic mechanisms of RCCs that lack VHL inactivation, which constitute approximately 40% of the sporadic clear cell RCC cases (Foster et al, 1994;Gnarra et al, 1994;Herman et al, 1994;Shuin et al, 1994Shuin et al, , 1999. Notably, multivariate analysis of the clinicopathological parameters using a logistic regression model showed that HOXB13 methylation correlated significantly with tumor grade and microvessel invasion.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 30 000 newly diagnosed cases in the USA and 7000 occur in Japan every year. Previous studies revealed that the von Hippel-Lindau (VHL) gene is the major tumor suppressor gene that participates in the development of human RCC, as it is inactivated, mostly by genetic alterations, in about 60% of sporadic RCC cases (Foster et al, 1994;Gnarra et al, 1994;Herman et al, 1994;Shuin et al, 1994Shuin et al, , 1999. However, the tumorigenic mechanisms for the sporadic RCCs that lack VHL gene inactivation and the multi-step processes involved in RCC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Over half of all sporadic clear cell RCCs carry biallelic inactivation of both VHL alleles (Foster et al, 1994;Gnarra et al, 1994;Shuin et al, 1994). However, the molecular pathway by which the VHL protein (pVHL) modulates the expression of target genes leading to tumorigenesis cannot be explained for all cases of clear cell RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the VHL gene, which is the first causative gene identified for VHL syndrome, are detectable in 30-60% of sporadic clear cell RCCs (Gnarra et al, 1994;Shuin et al, 1994;Schraml et al, 2002). Furthermore, inactivation of VHL through methylation or loss of heterozygosity (LOH) occurs frequently in clear cell RCC (Herman et al, 1994;Moch et al, 1998;Brauch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%